2019
DOI: 10.1002/cncr.31987
|View full text |Cite
|
Sign up to set email alerts
|

Impact of patient choice and hospital competition on patient outcomes after prostate cancer surgery: A national population‐based study

Abstract: Background Policies that encourage patient choice and hospital competition have been introduced across several countries with the purpose of improving the quality of health care services. The objective of the current national cohort study was to analyze the correlation between choice and competition on outcomes after cancer surgery using prostate cancer as a case study. Methods The analyses included all men who underwent prostate cancer surgery in the United Kingdom between 2008 and 2011 (n = 12,925). Multilev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…Geographic level factors consisted of median household income (reported by quartiles of the patient's ZIP code and acquired from AHRF), Herfindahl-Hirschman index (defined as the sum of square market shares of inpatient days measured in a county, 34 which was obtained from AHA survey), and state-fixed effects. 35,36…”
Section: Covariatesmentioning
confidence: 99%
“…Geographic level factors consisted of median household income (reported by quartiles of the patient's ZIP code and acquired from AHRF), Herfindahl-Hirschman index (defined as the sum of square market shares of inpatient days measured in a county, 34 which was obtained from AHA survey), and state-fixed effects. 35,36…”
Section: Covariatesmentioning
confidence: 99%
“…The authors noted that patient mobility occurred in the absence of validated measures of care quality and concluded that competition between hospital trusts for patients may be creating disparities in access to care. Nevertheless, in a separate study by the same team using data from 2008 to 2011, it was noted that competition appeared to improve short-term patient outcomes [23]. Both studies predate our present data collection period, and it is possible that the more widespread availability of RARP has helped reduce the desire to bypass local providers, and thus the disparities in access and outcomes reported in the earlier studies.…”
Section: Discussionmentioning
confidence: 69%
“…It is also notable that we found no published articles focusing on how the reform has affected costs, efficiency and continuity. A lack of evidence of improved efficiency and quality as a result of patient choice has previously been noted [ 63 ], but some studies have indicated a positive effect of competition on quality in specialised care [ 64 , 65 ].…”
Section: Discussionmentioning
confidence: 99%